Islamic Religious Teachers Roles in Drug Misuse Prevention Among Students at State Junior High Schools in Palu - Adawiyah Pettalongi; Nur Atika; Rusdin Rusdin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2022)
The focus of this research is the roles of Islamic teachers in the prevention of drug misuse by students of a state junior high school in Palu city, central Sulawesi. This study aims to determine what approaches and methods have been carried out by schools, especially Islamic religious education teachers, to prevent drug misuse by the students of the school. This study uses a qualitative approach with data collection was conducted through observation, interviews, and document studies. The data obtained was then analyzed through the data reduction and presentation techniques. The study found that the level of drug misuse by the students was relatively high. It was said that the school is a red zone. There were approximately 60 students exposed to drug abuse at the school in 2019. As for the prevention strategies, the school implemented several policies and programs such as conducting basic leadership training, full-day programs at school, religious coaching, and other positive activities. The approaches taken by Islamic religious education teachers in preventing drug abuse are pedagogic, cultural, personality psychology approaches, family involvement, emotional approaches, Islamic guidance, counseling approaches, and religiosity approaches.